2020
DOI: 10.1177/0003134820960073
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Mentoring Early in Surgical Practice

Abstract: Background Transitioning from trainee to independent surgeon is challenging, with teaching and mentoring learners adding complexity. This study aimed to identify benefits and challenges of teaching and mentoring residents early in surgical practice. Materials and Methods A mixed-methods survey with multiple choice and open-ended questions was developed for early career (first 3 years) and experienced (more than 3 years) surgeons working with residents. The survey was initially piloted by 6 surgeons, revised ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…During their training, students commonly witness the occurrence of safety events and unsafe practices [ 18 ], but they are unable to “speak up” during a critical situation in 56% of cases, even when they can do so [ 19 ]. Universities, and particularly student mentors, must transmit transferable skills to deal with such events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…During their training, students commonly witness the occurrence of safety events and unsafe practices [ 18 ], but they are unable to “speak up” during a critical situation in 56% of cases, even when they can do so [ 19 ]. Universities, and particularly student mentors, must transmit transferable skills to deal with such events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be related to the absence of time and safety stressors that are in the operating room, as it has been found that the operating room is felt to be the most challenging teaching setting due to attention to patient safety. 21 Negative feedback and questioning have potentially negative effects on trainees including loss of interest and lack of self-worth, and should be used minimally. 22 Regardless of the teaching trends identified here, surgical educators should also be reminded that learner-centered education is a tenet of adult learning theory 23 and that techniques and topics should be tailored to the individual learning needs of residents.…”
Section: Discussionmentioning
confidence: 99%